On-Site Deployment of an Air-Liquid-Interphase Device to Assess Health Hazard Potency of Airborne Workplace Contaminants: The Case of 3-D Printers - Kim, Boowook; Shin, Jae Hoon; Kim, Hoi Pin; Jo, Mi Seong; Kim, Hee Sang; Lee, Jong Sung; Lee, Hong Ku; Kwon, Hyuk Cheol; Han, Sung Gu; Kang, Noeul; Gulumian, Mary; Bello, Dhimiter; et al. (Frontiers in Toxicology, 2022)
Biomonitoring of workers is a way of evaluating workers’ exposure to chemicals and particulate materials by measuring biomarkers including chemicals, their metabolites, and reaction products in workers’ specimens. We have developed a cell-based biomonitoring device that can evaluate cytotoxicity and induction of biomarkers along with exposure concentration. This device is based on ALI (air-liquid interphase) and can be used to evaluate cytotoxicity and biomarker induction after exposure of 1-2 hr workplace air to the device. After exposure, cells on the transwell were processed to assess the induction of biomarkers from the exposed cells and cytotoxicity from the media. Initially, we estimated the deposition rate of particles to the filters in the transwell after exposing silver nanoparticles (AgNP 20-30 nm) for 2 hrs. A549 lung epithelial cells cultured on the transwell in the ALI device were exposed to AgNP for 2 hrs and evaluated for cytotoxicity and induction of pro-inflammatory cytokines. The cells in the ALI device were exposed to 3-D printer emissions in the workplace and evaluated for cytotoxicity and induction of pro-inflammatory cytokines. Two-hour exposure and thereafter 24 hr incubation of positive control of AgNP increased LDH and microprotein level significantly. In addition, with 2-hr exposure of the positive control AgNP, the mRNA levels for IL-1, IL-6, and TNF-α increased significantly (P>0.01-0.05), and the levels of for IL-1, IL-6 (p<0.05), and TNF-α also increased after 24 hr post-exposure. The cytotoxicity evaluation tests conducted for 3-D printer emissions at 810 and 957 ㎍/m3, more than 80 times higher than the TSP concentration at workplace air concentration (9-12.5 ㎍/m3) suggested no significant cytotoxicity after 2-hr 3-D printing emission exposure and thereafter 24-hr post-exposure incubation. Hyperspectral microscopic observation showed the 3-D printer emitted particles were associated with A549 cells after 2-hr exposure, and many particles were internalized in A549 cells after 24-hr additional incubation. Pro-inflammatory cytokine mRNA IL-1b and IL-6 increased significantly after 2-hr exposure and thereafter 24-hr incubation for IL-6, while TNF-α decreased significantly after 2-hr exposure and after 24-hr incubation. These results suggested that the ALI device may be used as the alternative to workers’ biomonitoring in the workplace.